Factors associated with compensation strategy on rural workers in urban areas: Analysis of "Mingong" in construction sector in China - Liu, Er (2008)
Workers' compensation is a very important issue for an organization's development. The objective of this research is to examine which factors will influence workers' compensation, and also to examine what relationship between these influence factors and workers' compensation in construction enterprises in China. The literature review provides plenty of studies about this area which have done by others researchers. The respondents were based on a sample population. The questionnaires were constructed out of extensive literature review. And the hypotheses were tested by using SPSS program of reliability analysis, descriptive analysis and multiple regressions. This research discovered that work-related risks, workers' performance, and workers' competency have a positive significant impact on workers' compensation, age and gender has a significant impact, and organization size still have an impact on employee compensation but not significant.